2008
DOI: 10.1080/13623690802373884
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a hospital based injury surveillance system in Africa: lessons learned

Abstract: A multinational injury surveillance pilot project was carried out in five African countries in the first half of 2007 (Democratic Republic of the Congo, Kenya, Nigeria, Uganda and Zambia). Hospitals were selected in each country and a uniform methodology was applied in all sites, including an injury surveillance questionnaire designed by a joint programme of the Pan American Health Organization and the United States Centres for Disease Control and Prevention. A total of 4207 injury cases were registered in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…More than half of the patients admitted to an emergency department of a hospital sustained road traffic injuries similar to previous studies in low and middle income countries countries (Yamuragiye et al 2013; Uthkarsh et al 2012; Chinh et al 2007; Zavala et al 2008; John et al 2008). However few studies have reported fall injury as the most common mechanism of injury (Musharrafieh et al 2011; Cardona et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…More than half of the patients admitted to an emergency department of a hospital sustained road traffic injuries similar to previous studies in low and middle income countries countries (Yamuragiye et al 2013; Uthkarsh et al 2012; Chinh et al 2007; Zavala et al 2008; John et al 2008). However few studies have reported fall injury as the most common mechanism of injury (Musharrafieh et al 2011; Cardona et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…33 Further, a multinational surveillance study carried out in five countries in sub-Saharan Africa demonstrated a similar proportion of injuries due to RTA as in the current study. 41 As RTAs are the global epidemiologic driver for the increase in deaths due to trauma, their predominance as a mechanism in the present study highlights their importance in the Haitian setting. 2 Although these data are limited, the findings suggest that interventions aimed at prevention and treatment of RTA may be an efficacious public health endeavor in the Northeast region.…”
Section: Discussionmentioning
confidence: 84%
“…The proportion of injuries (51%) due to violence (suicide and homicide) was higher than most reported in the region. A hospital-based study in Democratic Republic of the Congo, Kenya, Nigeria, Uganda, and Zambia revealed that 40% of injury deaths were due to violence,29 while another study in five Kampala Hospitals Uganda showed that deaths due to violence related injuries accounted for only 14% 30. While these differences might reflect the reality in terms of occurrence of deaths due to violence, it might also be a measurement issue.…”
Section: Discussionmentioning
confidence: 99%